The Linguistics of Giving. - Newman, John (Typological studies in language ;, 1998)
In this collection of papers twelve linguists explore a range of interesting properties of 'give' verbs. The volume offers an in-depth look at many morphological, syntactic, and semantic properties of 'give' verbs, including both literal and figurative senses, across languages. Topics include: an apparent zero-morpheme realisation of 'give' in a Papuan language; noun plus causative-like suffix expressing the 'give' concept in Nahuatl; 'give' and other ditransitive constructions in Zulu; the complex verbal morphologies associated with 'give' verbs in Chipewyan, Cora, and Sochiapan Chinantec; th.